Angiotensin I-converting enzyme inhibitory peptide: an emerging candidate for vascular dysfunction therapy. (4th July 2022) - Wu, Qiang; Luo, Feijun; Wang, Xiao-Ling; Lin, Qinlu; Liu, Gao-Qiang
Abstract: Abnormal vasoconstriction, inflammation, and vascular remodeling can be promoted by angiotensin II (Ang II) in the renin–angiotensin system (RAS), leading to vascular dysfunction diseases such as hypertension and atherosclerosis. Researchers have recently focused on angiotensin I-converting enzyme inhibitory peptides (ACEIPs), that have desirable efficacy in vascular dysfunction therapy due to Ang II reduction by inhibiting ACE activity. Promising methods for the large-scale preparation of ACEIPs include selective enzymatic hydrolysis and microbial fermentation. Thus far, ACEIPs have been widely reported to be hydrolyzed from protein-rich sources, including animals, plants, and marine organisms, while many emerging microorganism-derived ACEIPs are theoretically biosynthesized through the nonribosomal peptide synthase (NRPS) pathway. Notably, vasodilatation, anti-inflammation, and vascular reconstruction reversal of ACEIPs are strongly correlated. However, the related molecular mechanisms underlying signal transduction regulation in vivo remain unclear. We provide a comprehensive update of the ACE-Ang II-G protein-coupled type 1 angiotensin receptor (AT1R) axis signaling and its functional significance for potential translation into therapeutic strategies, particularly targeting AT1R by ACEIPs, as well as specific related signaling pathways. Future studies are expected to verify the biosynthetic regulatory mechanism of ACEIPs via the NRPS pathway, the effect of gut microbiota metabolism on vascular dysfunction and rigorous studies of ACE-Ang II-AT1R signaling pathways mediated by ACEIPs in large animals and humans.